Analisis Metode Pembelajaran yang Efektif pada Materi SKI Kelas XI di MAN 1 Surakarta Tentang Pembaharuan Islam di Indonesia - Oktaviana Nur Dewanti (Publikasi Indonesia, 2023)
This study aims to analyze effective learning methods on Islamic Cultural History (SKI) material in class XI at MAN 1 Surakarta about Islamic Renewal in Indonesia. The literature study method was used in this study by collecting and analyzing various literature related to learning methods that are relevant to the material. The results of the analysis show that the discussion method and the case study method can be effective alternative learning methods in presenting material on Islamic renewal in Indonesia to students. The discussion method can facilitate interaction between teachers and students, as well as between students, which can encourage students to think critically and be active in the learning process. The case study method can link theory with concrete practice and help students explore information about the context, factors, and impact of Islamic renewal through case study analysis. However, the use of learning methods must be adapted to the characteristics of students, learning objectives, and available resources in the MAN 1 Surakarta environment. Evaluation and adjustment of the learning methods applied are also important to ensure the effectiveness and sustainability of the learning process. This study provides recommendations to teachers or other educational institutions to use discussion and case study methods as an alternative effective learning method in presenting material on Islamic renewal in Indonesia to students. This conclusion is based on an analysis of literature studies and further research is needed with a more comprehensive method to strengthen the results of this study.